HIF-2α level in adolescents with chronic inflammatory pathology of the upper gastrointestinal tract - N. S. Shevchenko; N. V. Krutenko; L. L. Sukhova; O. M. Tsiura; H. O. Shlieienkova; K. V. Voloshyn (The Ukrainian Biochemical Journal)
Сhronic inflammatory diseases of the gastrointestinal tract are among the most common pathological conditions in adolescents. A significant role in the pathogenesis of gastrointestinal tract diseases is given to the functioning of the oxygen sensor system, the main mediator of which is hypoxia-inducible factor 2 (HIF-2α). Therefore, the purpose of the study was to determine the level of HIF-2α in the plasma of patients with chronic inflammatory pathology of the gastrointestinal tract, taking into account the endoscopic picture of the lesion, localization of the pathological process, age and gender of the patient. The study involved 70 adolescents aged 8-18 years with chronic gastroduodenitis (CGD), gastroesophageal reflux disease (GERD), gastric or duodenal ulcer and 25 peers who had been classified as healthy. The plasma concentration of HIF-2α was measured by a sandwich-linked ELISA. Helicobacter pylori infection was determined by urease test or by ELISA. According to the data obtained, the HIF-2α plasma level was higher in patients with chronic inflammatory gastrointestinal disease compared to the control group. In boys with chronic gastroduodenal disease, the level of HIF-2α was higher than in girls. CGD and GERD were characterized by a higher HIF-2α level in plasma than gastric and duodenal ulcers. The HIF-2α level did not depend on the age of the patients or the presence of Helicobacter pylori infection.